Physicochemical and thermal properties of gamma-irradiated sago (Metroxylon sagu) starch. (April 2015) - Othman, Zainon; Hassan, Osman; Hashim, Kamaruddin
Abstract: Sago ( Metroxylon sagu ) starch was exposed to gamma-irradiation in air at doses 6, 10 and 25 kGy. Subsequent changes in the physicochemical and thermal properties were measured. The apparent amylose content and swelling power of irradiated sago starch was significantly reduced while reducing sugars and starch solubility were significantly increased due to degradation. X-ray diffraction studies showed that radiation did not affect the crystalline type but induced a decrease in the degree of crystallinity, indicating the destruction of the ordered distribution of neighboring polysaccharide chains in the starch granules, in particular of the amylopectin component, which is responsible for starch crystallinity. Differential scanning calorimetry (DSC) of irradiated sago starch showed a small but significant increase in the onset and peak transition temperatures at 10 and 25 kGy dose; the conclusion temperature and gelatinization enthalpy was not affected. SEM and particle size analysis produced no evidence of physical damage to sago starch up to 25 kGy dose radiation treatment since the granular appearance and size distribution was retained. Highlights: Properties of irradiated sago starch at doses 0, 6, 10 and 25 kGy were studied. Apparent amylose content and swelling power was reduced by irradiation Irradiation decreased relative crystallinity but did not alter the crystalline type. SEM of irradiated starch granules up to dose of 25 kGy showed no physical damage. Thermal properties of irradiated sago starch were slightly affected.